Resisting Marginalisation in the Select Short Stories of Bessie Head - Hussain, Noor; Zaman, Nazia (Integrated Journal for Research in Arts and Humanities, 2024)
The African black woman is said to suffer from double marginalisation –marginalized by colonialism and by patriarchy. Bessie Head, one of the most influential authors of South Africa, voices the marginalization faced by the women of her country. In her works, she narrates the tales of underprivileged village women and their predicament to exist as mere humans in their own society and among their own people. Though she does not consider herself a feminist, her protagonists are always females and they become the mouthpiece of the entire subjugated section of the society. Head’s short stories depict the breakdown of traditional structures of the society and also the erosion of security that the institution of marriage offered to the women. This paper is an attempt to study two of her short stories to highlight the suffering of her protagonists and also how they overcome them and present a new image of themselves.